A New Jurassic Kempynine Species With Notes on Historical Distributions of Kempyninae Integrated Both Fossil and Extant Taxa (Neuroptera: Osmylidae) - Ma, Yiming; Shih, Chungkun; Ren, Dong; Wang, Yongjie (Frontiers in Ecology and Evolution, 2022)
The extant kempynines, a strict “southern group”, are confined in South America and Australia, while their most fossil relatives are abundantly recorded in the Northern Hemisphere. This pattern of the biogeographic distribution implies the complicated evolutionary scenario of Kempyninae. Herein, a new northern species Arbusella platyptera Ma & Wang, sp. nov. is described from the Jiulongshan Formation in Daohugou, Inner Mongolia, China. Additionally, a key to the extinct species and extant genera of Kempyninae is provided. Integrating all extant and most fossil genera of Kempyninae, we conducted phylogenetic analyses to explore the inner relationships of Kempyninae for the first time. The results corroborate the monophyly of Kempyninae, and retrieve three clades within the subfamily, viz. two northern fossil genera (†Arbusellla + †Jurakempynus) constituting the basalmost clade; three other northern fossil genera (†Sauktangidae + †Mirokempynus + †Ponomarenkius) forming a monophylic clade, which is sister to the third clade consisting of all extant southern genera and the southern fossil genus of †Euporismites. And the extant kempynines was hypothesized to evolve independently from their northern Mesozoic relatives. The Dispersal-vicariance (DIVA) analysis revealed a northern and prepangean origin of Kempyninae, and the northern ancestral kempynines first colonized the South Hemisphere before the split of Pangea. Our results expose a more complicated evolutionary scenario of the insects with a long evolutionary history, and provide the new insight to understand the distribution pattern formation of current relictual insects.